Veliki faktor osebnosti - Musek, Janek (Anthropos (Ljubljana), 2011)
Structural models have been developed in both cognitive and conative fields of personality. Very recently, the empirical psychological research yielded the results that convincingly show the existence and importance of the General Factor of Personality (GFP or the Big One) in the Big Five domain. Consequently, the existent hierarchical models of personality strusture should be modified to the essential extent. Moreover, the question arises, whether GFP is in the essence a representative of still more general factor underlying the entire conative sphere of personality. In this study, the structural multivariate analyses of the 19 very complex psychological variables (including the Big Five, self-concept and self esteem, self-discrepancies, self-construals, gender shema, emotionalizy, well-being and psychological health) have been conducted. The results convinvingly demonstrated the existence of a distinctive general favtor at the apex of the structural hierarchy of the variables in the model. This factor has been interpreted as the Big Factor of Personality (BFP). The BFP correlated very highly with the GFP, yet encompasses some significant additional information. Thus, the results of the study corroborated the idea of a very general dimension underlying the entire non-cognitive domain of personality.
Keywords: osebnost; personality; osebnostna struktura; osebnostne lastnosti; psihologija osebnosti